Implementasi Manajemen Kesiswaan dalam Mendukung Peningkatan Prestasi Belajar Siswa di MAN 4 Aceh Selatan - Diana, Eva; Azdillah, Muhammad Rizky (Pase: Journal of Contemporary Islamic Education, 2024)
The improvement of students’ learning achievement is influenced not only by internal factors of the learners but also by the effectiveness of student management implemented by educational institutions. This study aims to analyze the forms of student management implementation in supporting the improvement of students’ achievement at MAN 4 Aceh Selatan. This research employs a descriptive qualitative approach with a field research design. Data were collected through in-depth interviews, observations, and documentation. The research informants consisted of the principal, the vice principal for student affairs, and the vice principal for curriculum affairs. Data were analyzed inductively through the stages of data condensation, data display, and conclusion drawing, using triangulation techniques to ensure data validity. The findings indicate that the implementation of student management at MAN 4 Aceh Selatan covers four main aspects: (1) Planning, which is carried out by aligning students’ potentials and interests with various flagship programs such as Qur’an memorization (tahfiz al-Qur’an), Qur’anic recitation (tilāwah), and vocational skills; (2) Organizing, which is conducted collaboratively among school leaders and supervising teachers; (3) Implementation, which focuses on fostering students’ discipline, responsibility, and competitiveness; and (4) Evaluation, which is conducted periodically through meetings and performance monitoring. The school culture developed through the slogan “Madrasahnya Para Juara” (“The School of Champions”) encourages high learning motivation and a strong spirit of achievement among students.